2017
DOI: 10.1136/bmjopen-2016-012546
|View full text |Cite
|
Sign up to set email alerts
|

Association of comorbidity and health service usage among patients with dementia in the UK: a population-based study

Abstract: BackgroundThe majority of people with dementia have other long-term diseases, the presence of which may affect the progression and management of dementia. This study aimed to identify subgroups with higher healthcare needs, by analysing how primary care consultations, number of prescriptions and hospital admissions by people with dementia varies with having additional long-term diseases (comorbidity).MethodsA retrospective cohort study based on health data from the Clinical Practice Research Datalink (CPRD) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
134
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 134 publications
(148 citation statements)
references
References 17 publications
7
134
0
7
Order By: Relevance
“…Recent studies have focused on the number of comorbidities and hospitalization rates in the UK and Canada. These studies showed that an increased number of comorbid disorders led to a higher frequency of hospitalization, although neither study differentiated between psychiatric or somatic departments …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies have focused on the number of comorbidities and hospitalization rates in the UK and Canada. These studies showed that an increased number of comorbid disorders led to a higher frequency of hospitalization, although neither study differentiated between psychiatric or somatic departments …”
Section: Discussionmentioning
confidence: 99%
“…[33][34][35][36][37] Some studies have focused on a higher use of psychiatric and medical inpatient treatment among dementia patients with further psychiatric comorbidities, 37 but little research has been conducted on the effect of cardiovascular and metabolic comorbidities. 33 Recent studies have focused on the number of comorbidities and hospitalization rates in the UK and Canada. These studies showed that an increased number of comorbid disorders led to a higher frequency of hospitalization, although neither study differentiated between psychiatric or somatic departments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 Some people with dementia may also be prescribed medication for comorbid health conditions such asType 2 Diabetes Mellitus or high blood pressure. 11 Unsurprisingly, given their cognitive problems, managing medication is complex for people with dementia which can result in "medication errors, medication related hospital admissions, and dependence on others to assist with medication management tasks". 12 Although non-adherence to medication is a widespread problem across conditions, ages, and other demographics, and can be intentional or unintentional, 13 cognitive impairment and dementia have been shown to specifically impact on medication adherence.…”
Section: This Fig-mentioning
confidence: 99%
“…Although there is currently no cure for dementia, medicines play a key role in the lives of people with dementia, primarily to manage symptoms . Some people with dementia may also be prescribed medication for comorbid health conditions such as Type 2 Diabetes Mellitus or high blood pressure . Unsurprisingly, given their cognitive problems, managing medication is complex for people with dementia which can result in “medication errors, medication related hospital admissions, and dependence on others to assist with medication management tasks” .…”
Section: Introductionmentioning
confidence: 99%